SIFAT ANTIRAYAP EKSTRAK KULIT BIJI SAGA (Adenanthera pavonina Linn) Antitermites Properties Of Extract Shell Seed Saga (Adenanthera pavonina Linn) - Lensi Mian Sinaga; Rudi Hartono; Luthfi Hakim (Peronema Forestry Science Journal, 2013)
The aims of these research were to know the extract content of saga seed shell, to evaluated weight lost of cellulose paper, to evaluated mortality of termites and to evaluated termites consumption. Research was done by extracting sample with methanol then partitioning with n-hexane. Concentrated extractive  of 2%, 4%, and 6% were used the toxic test of the termite Coptotermes curvignathus. The Result showed that extract content  of saga seed shell was 15.82%. Mortality with concentration of 2%, 4% and 6% were not significantly so the concentration of 2% was effective, eficien and happened in 6th day. The tendency showed that increasing concentration of extract caused decreasing of weight lost of cellulose paper and consumption of termites. The percentage weight lost of cellulose paper was 3.88%–11.04% and consumption of termite was 0.26–0.73 mg. The extract with concentration of 2% was effective based of evaluated from mortality, weight lost of cellulose paper and rate consumption of termites. Keyword : Saga, Extractive, Concentration, Toxic, Termites